PEMETAAN SEBARAN STATUS UNSUR HARA N, P DAN K PADA LAHAN SAWAH DI KECAMATAN TUREN, KABUPATEN MALANG - Christanti Agustina; Mochtar Rayes; Marinda Kuntari (Jurnal Tanah dan Sumberdaya Lahan, 2020)
The availability of nutrients plays a role in increasing crop productivity, especially primary macronutrients (nitrogen, phosphorus and potassium). This research aimed to measure the content of macronutrients and crop productivity in the rice field and to map the nutrients status. The study was conducted from July to October 2019 in Turen District. The survey method based on the boundary of the land mapping unit was used to collect field data in this study. The mapping of nutrient status created using IDW, which was interpolated data based on the assumption that values of unsampled points can be predicted as the weighted average of known values within the neighbourhood. The results showed that the nitrogen status are very low to low status (0.08% - 0.18%), the phosphorus status are very low to low status (4.5 mg kg-1 – 12.37 mg kg-1) and the potassium status are at low, moderate to high status (0.25 cmol kg-1 – 0.71 cmol kg-1). The availability of nitrogen nutrient is classified as S2, the availability of phosphorus nutrient is classified as S3, and the availability of potassium nutrient is classified as S1. The availability of nitrogen, phosphorus and potassium can be increased through fertilization in accordance with the needs and recommendations. The effect of the status of nitrogen, phosphorus and potassium at the end of planting on crop productivity was indicated by the regression coefficient of R2 = 0.0826.